Genealogi Transmisi Keilmuan Pesantren: Melacak Akar Pedagogi Kitab Ta'lim Muta'allim dari Era Nubuwah Hingga Tradisi Pesantren di Nusantara - Ahmad Wafa Izzulhaq Al Aziz (IIQ An Nur Yogyakarta, 2026)
This research aims to trace the genealogy of the pedagogical transmission of the book Ta’lim al-Muta’allim and to dissect the sociological reasons behind its fundamental position in the pesantren education system in Indonesia. Using a qualitative-descriptive method with a library research approach, this study is analyzed through Peter L. Berger’s sociology of knowledge framework to examine the processes of externalization, objectivation, and internalization of values within the pesantren. The results indicate that Ta’lim al-Muta’allim is a crystallization of the prophetic pedagogical tradition transmitted through the Nusantara ulama network (Haramain) in the 19th century. The prioritization of adab as a prerequisite before studying